Coupling coordination analysis of green finance and industrial technology innovation: A case study in Zhejiang Province, China - Wang, Wenjing; Lin, Jingcheng; He, Taiyi; Zhao, Haoxiang; Zhao, Xin (Frontiers in Environmental Science, 2022)
Both green finance and industrial technology innovation play irreplaceable roles in the framework of sustainable development. Research on the coupling and coordination between these systems will deepen the realization of sustainable development models. This study applied the TOPSIS entropy weight method to measure the development of green finance and industrial technology innovation in Zhejiang Province between 2012 and 2019 and used the coupling coordination degree model to determine the strength and effect of the interaction between these systems in Zhejiang Province. The results showed strong regional heterogeneity in the development of green finance and industrial technology innovation in the nine cities in Zhejiang Province within the study period. Moreover, mutual assistance and correlation between green finance and industrial technology innovation in the nine cities of Zhejiang Province increased over time. Finally, the effect of green finance and industrial technology innovation in the nine cities of Zhejiang Province was complex. The results of this study may inform policy suggestions regarding the roles potential roles of the government, commercial banks, and enterprises.